IR Bagendit Paddy Leaves Extract Improves Liver Cell Morphology and Reduces The Activity of Transaminase Enzymes After Lead Exposure in Rat - Budi Santosa; Henna Ria Sunoko; Andri Sukeksi; Siti Thomas Zulaikhah (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Lead (Pb) was known as one of systemic toxic agent. In the body, lead may be deactivated by the metallothioneins. Paddy leaves contain metallothioneins, sugars and pythosterols, and studies have shown the pharmacological activity of rice leaves on the protective effect of lead-induced rats against kidney function. The aim of this study was to evaluate the role of IR Bagendit paddy leaves extract as hepatoprotective agent.METHODS: Twenty-eight rats were divided into four groups: one control and three treatment groups. Control and treatment groups were exposed to lead of 0.5 g/kg body weight (BW)/day and then the treatment groups were administered with paddy leaves extract of 0.2; 0.4; and 0.8 g/kg BW/day per oral for 8 weeks. On the last day of the 8th week, body weight was measured and the numbers of normal, degenerative and necrotic liver cells were examined with hematoxylin-eosin staining. Serum glutamic oxaloacetic transaminase (SGOT) and serum glutamic pyruvic transaminase (SGPT) were measured as liver function parameter. Difference of variables between control and treatment groups were examined by Friedman test.RESULTS: There was no association in different BW between groups. The normal liver cells are higher in treatment than control group (p<0.001) and necrotic liver cells are lower in treatment than control group (p≤0.001). There was no association in degenerative liver cells between groups (p=0.153). The activity of transaminase enzymes are lower in treatment than control group (p<0.001).CONCLUSION: IR Bagendit Paddy leaves extract reveals hepatoprotective activity by improving liver cells morphology and reducing the activity of transaminase enzymes after lead exposure.KEYWORDS: paddy leaves extract, liver normal cell, necrotic cell, transaminase enzymes